IDENTIFYING SEEPAGE IN DITCHES AND CANALS IN POLDERS IN THE NETHERLANDS BY DISTRIBUTED TEMPERATURE SENSING - O. A. C. Hoes; W. M. J. Luxemburg; M. C. Westhof; N. C. van de Giesen; J. Selker (International Association of Lowland Technology, 2009)
Seepage in ditches and canals, a common feature in polders in The Netherlands, is investigated making use of temperature sensing by fiber optic cable. By its high spatial and temporal resolution capabilities the technique reveals the complex ensemble of all effects that define the water temperature on the bottom of the watercourses in three polders where a 1300 m long cable was located. From the temperature signature the location of suspected seepage zones in the water courses can be determined more precisely. The study shows that the sensing of seepage through temperature is time dependent as the signature can temporarily fade and can be extremely localized. This shows the potential for the applied technique.